Search for anomalous ZZγ and Zγγ couplings in the process e+e- → Zγ at LEP - Dova, María Teresa (2000)
We search for anomalous trilinear gauge couplings in the ZZγ and Zγγ vertices using data collected with the L3 detector at LEP at a centre-of-mass energy<mtext>s</mtext><mtext>=189</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>. No evidence is found and limits on these couplings and on new physics scales are derived from the analysis of the process e+e−→Zγ.